Prevalence of low back pain and associated factors in adults from a middle-size Brazilian city - Zanuto, Everton Alex Carvalho [UNESP]; Codogno, Jamile Sanches [UNESP]; Christófaro, Diego Giulliano Destro [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Cardoso, Jefferson Rosa; Fernandes, Romulo Araújo [UNESP] (ABRASCO - Associação Brasileira de Saúde Coletiva, 2015)
Objective: To determine the prevalence of low back pain and some related variables among adults of both genders. Methods: Was conduct a cross-sectional study of population-based in the urban area of Presidente Prudente, São Paulo. The sample consisted of 743 adult residents for over two years in this city. Low back pain, quality of sleep and physical activity were collected through face to face interview at the residence of respondents. Was used the chi-square test to analyze the association between variables, later was created tree multivariate models with hierarchical inclusion of confounding factors. Results: The prevalence of low back pain reported last year was 50.2% (95% CI: 46.6, 53.8), and the last week 32.3% (95% CI: 28.9, 35.6). Was association among low back pain and females (p-value = 0.031), older age, lower education, altered sleep and overweight, the adjusted model found that people over the age of 45 years (45 to 59.9 years, OR = 13.1 [1.72-98.5] and ≥ 60 years, OR = 9.10 [1.15-71.7]), with some alteration of sleep (OR = 3.21 [1.84-5.61]) and obese (OR = 2.33 [1:26 to 4:33]) seems to be a risk group for low back pain. Conclusion: The prevalence of low back pain is high and obese people aged over 45 years, with any sleep disturbance are a group at higher risk for low back pain.

Objetivo: Determinar a prevalência de dor lombar e algumas variáveis relacionadas entre adultos de ambos os sexos. Métodos: Estudo transversal de base populacional na zona urbana de Presidente Prudente, São Paulo. A amostra foi composta por 743 adultos, dor lombar, qualidade do sono e atividade física foram coletadas por meio de entrevista face a face na residência dos entrevistados. Utilizou-se o teste qui-quadrado para analisar a associação entre as variáveis, depois foram criados três modelos multivariados com inserção hierárquica dos fatores de confusão. Resultados: A prevalência de dor lombar relatada no último ano foi de 50,2% (IC95%: 46,6; 53,8), e na última semana 32,3% (IC95%: 28,9; 35,6). A dor lombar associou-se com sexo feminino, maior idade, menor escolaridade, sono alterado e excesso de peso, o modelo ajustado identificou que pessoas com idade superior a 45 anos (45-59,9 anos, OR= 13.1 [1.72-98.5] e ≥ 60 anos, OR= 9.10 [1.15-71.7]), com alguma alteração de sono (OR= 3.21 [1.84-5.61]) e obesos (OR= 2.33 [1.26-4.33]) parecem um grupo de risco para dor lombar. Conclusão: A prevalência de dor lombar é alta em pessoas obesas com idade superior a 45 anos que possuem alterações no sono, formando o grupo de maior risco para esse mal.
Prevalência de dor lombar e fatores associados entre adultos de cidade média brasileira
Keywords: Low back pain; Exercise; Sleep; Body mass index; Dor lombar; Exercício; Sono; Índice de massa corporal